2009
DOI: 10.1007/s11104-008-9863-2
|View full text |Cite
|
Sign up to set email alerts
|

NiO(s) (bunsenite) is not available to Alyssum species

Abstract: To determine if the Ni-hyperaccumulator Alyssum corsicum can absorb Ni from the kinetically inert crystalline mineral NiO(s) (bunsenite). A. corsicum and A. montanum plants were grown for 30 days in a serpentine Hoagland solution. NiO was provided at 0 or 0.1 g L −1 (1.34 mmol L −1 ) as reagent grade NiO particles <1 μm diameter, continuously mixed by aeration. A. corsicum and A. montanum shoots contained 19.4 and 5.2 mg Ni kg −1 DW with NiO, and 3.0 and 1.1 mg Ni kg −1 DW shoots, respectively in the control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The Ni as an activator of the enzyme urease allows plants to utilize nitrogen from urea. There are some opinions that as Ni 2+ is absorbed by roots, a diffusion depletion zone is formed in the rhizosphere and Ni 2+ is released from solid or soluble bound forms to maintain soil solution equilibria (FELLET et al, 2009). According to some studies the normal plants and crop species generally contain 1-5 mg Ni kg -1 (BROOKS, 1987;CHANEY et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…The Ni as an activator of the enzyme urease allows plants to utilize nitrogen from urea. There are some opinions that as Ni 2+ is absorbed by roots, a diffusion depletion zone is formed in the rhizosphere and Ni 2+ is released from solid or soluble bound forms to maintain soil solution equilibria (FELLET et al, 2009). According to some studies the normal plants and crop species generally contain 1-5 mg Ni kg -1 (BROOKS, 1987;CHANEY et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…NiO was likely a form emitted from the nickel refinery. A basic test of whether Alyssum roots could dissolve this comparatively inert compound showed that Alyssum accumulated negligible Ni during a month of root exposure to 1 mm NiO particles [51]. Phytoextraction cannot deal with NiO or similar kinetically inert metal species.…”
Section: Phytomining Soil Nickelmentioning
confidence: 99%